Desafios do direito do comércio internacional na contemporaneidade em face do aquecimento global - Sampaio, Martim de Almeida (2007)
The sovereignty concept, beyond the centuries had acquired different meanings. Since the 20th Century, its concept have changed into a juridical category. After 1945, news States have emerged in the international field, as well the international organizations, and its have caused a profound changing in the sovereignty concept. Added to this fact, a new phenomena, designed by globalization affected dramatically the human, political, juridical and social relationship. The capitalism had experienced a cycle of prosperity, bringing with it a new problem to be faced by the humanity named global warming. The present paper ash to analyze different views to conclude, at last that the solution of this problem is over the juridical boundaries, as well the sustainable development, proposing a new and multidisciplinary view